2022
DOI: 10.1021/acsami.1c17861
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanorods with Spatial Separation of CeO2 Deposition for Plasmonic-Enhanced Antioxidant Stress and Photothermal Therapy of Alzheimer’s Disease

Abstract: Activities of catalase (CAT) and superoxide dismutase (SOD) of ceria nanoparticles (CeO2 NPs) provide the possibility for their application in nervous system oxidative stress diseases including Alzheimer’s disease (AD). The addition of hot electrons produced by a plasma photothermal effect can expand the photocatalytic activity of CeO2 to the near-infrared region (NIR), significantly improving its redox performance. Therefore, we coated both ends of gold nanorods (Au NRs) with CeO2 NPs, and photocatalysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 54 publications
(77 reference statements)
0
31
0
Order By: Relevance
“…Multiple literatures reported that the antioxidant activity of CeO 2 NPs mainly comes from the autocatalytic properties of CeO 2 . , Han et al proposed CeO 2 /Mn 3 O 4 nanocrystals as antioxidants for radiation protection. Mn ions form a strained Mn 3 O 4 layer, which increases the number of oxygen vacancies in the CeO 2 phase.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple literatures reported that the antioxidant activity of CeO 2 NPs mainly comes from the autocatalytic properties of CeO 2 . , Han et al proposed CeO 2 /Mn 3 O 4 nanocrystals as antioxidants for radiation protection. Mn ions form a strained Mn 3 O 4 layer, which increases the number of oxygen vacancies in the CeO 2 phase.…”
Section: Resultsmentioning
confidence: 99%
“…[175] Furthermore, due to the SOD activity, CeNP@MnMoS 4 can protect cells from oxidative stress. Based on the catalase and superoxide dismutase activity of CeO 2 and the hot electrons produced by gold nanorods, Ge et al [176] designed dumbbell-shaped nanocomposites (Au-CeO 2 ) by coating both ends of gold nanorods with CeO 2 NPs, and endowed Au-CeO 2 with photocatalysis and photothermal therapy in the NIR (Figure10 A). To further improve the therapeutic efficiency of Au-CeO 2 , the authors used the Aβ-targeted peptides (KLVFF) to modify Au-CeO 2 and obtained an Aβ-targeted nanocomposite (K-CAC).…”
Section: Gold Nanoclustersmentioning
confidence: 99%
“… 175 Furthermore, due to the SOD activity, CeNP@MnMoS 4 can protect cells from oxidative stress. Based on the catalase and superoxide dismutase activity of CeO 2 and the hot electrons produced by gold nanorods, Ge et al 176 designed dumbbell-shaped nanocomposites (Au-CeO 2 ) by coating both ends of gold nanorods with CeO 2 NPs, and endowed Au-CeO 2 with photocatalysis and photothermal effects in the NIR ( Fig. 10A ).…”
Section: Zero-dimensional Nanomaterialsmentioning
confidence: 99%
“…It is ideal to develop a multiple funcional probe, which could simultaneously and efficiently detect different biomakers. (4) There is still a lack of probes that can combine NIR fluorescence imaging with other conventional phototherapies such as photodynamic and photothermal therapy, [166][167][168][169][170][171][172] although they would be good candidates for AD theranostics. Therefore, the design of such probes would be a new direction for future researchers.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%